PENGENALAN KULIT KOPI TERFERMENTASI SEBAGAI PAKAN KELINCI DI DESA RIANG GEDE, KECAMATAN TABANAN, KABUPATEN TABANAN - Nuriyasa, I. M.; Mastika, I. M.; Dewi, G. A. M. K.; Suryani, N. N.; Puspani, E; Candrawati, D. P. M. A (Buletin Udayana Mengabdi; Vol 13 No 2 (2014): Jurnal Udayana Mengabdi, 2014)
Farmers in Riang Gede village, Tabanan District, Tabanan regency generally raise rabbits traditionally by providing grass field as basic feed and concentrate supplementation very minimum. Short course on diet manufacturing techniques in the form of pellets was performed in Juni 2014, aims to introduce the feed pellets, according to the rabbit nutrient requirements standard. Short course was suported by Tabanan Departement of Animal Production and Animal Sciense Post Gradute Program, Udayana University. This training introduces fermented of coffee leather as rabbit diet formulation in pellet form. There were 18 local famers and 9 farmer’s wife and 5 Riang Gede community leaders. The teams presented about (1) Rabbit nutrient requirment, (2) Prospect of rabbit, (3) energy and protein balance, (4) rabbit desease dan (4) diet manufacturing techniques in the form of pellets. Farmers can understand the course material and interested in creating a diet in the form of pellets. Based on the limited discussion, it could be seen that participants were very enthusiastic in joining this activity. They used this occasion for making discussion with the concerned team from Udayana University. Keywords: fermented coffee pulp, rabbit nutrien requirement standard, diet manufacturing techniques in the form of pellets.